Serum brain natriuretic peptide (BNP) and N-terminal brain natriuretic peptide (NT-proBNP) in heart valve disease - Moolman, J.A.; Du Preez, L.; Rossouw, G. (SA Heart Journal, 2017)
Serum levels of natriuretic peptides (BNP and NT- proBNP) are known to increase in cardiac failure, and aid in the diagnosis and management of such patients. BNP and NT-proBNP also increase in patients with heart valve lesions, and may contribute to the assessment and management of these patients. There appears to be a general trend towards higher BNP values in more severe heart valve lesions, but the exact implication of a raised BNP or NTproBNP appears to be different for each specific valve lesion. In aortic valve stenosis increased levels of BNP/NT-proBNP correlate with the degree of stenosis, symptoms and prognosis. In addition, the increased natriuretic peptide levels seem to reflect left ventricular dysfunction, as high levels predict poor long-term outcomes in conservatively treated patients as well as post-operative death and poor functional recovery in those who survive the valve replacement procedure. In mitral regurgitation natriuretic peptide levels correlate with the degree of valvular regurgitation, and seem to reflect subclinical left ventricular dysfunction. Serum natriuretic peptide levels are elevated in patients with mitral stenosis, and correlate with the degree of valvular stenosis and increased pulmonary pressure. Serum levels of natriuretic peptides are elevated in other heart valve lesions, such as aortic valve regurgitation, as well as different forms of mixed valvular disease, but very little is known about the relationship between the serum levels of natriuretic peptides and the latter valve lesions. The practical application of our knowledge concerning serum natriuretic peptides and heart valve disease is limited at this stage, and no specific cut-off values to guide patient management have been incorporated into any official guidelines as yet. This review aims to summarise current knowledge on serum BNP and NT–proBNP levels in patients with heart valve disease. The impact of this information on current clinical decision making in patients with different heart valve lesions, as well as evolving concepts concerning its potential future use, will be discussed.